Antiviral drug discovery for emerging diseases and bioterrorism threats (Wiley-Interscience, 2005)
Antiviral Drug Discovery gives readers a cutting-edge view of how chemical concepts are being mobilized to develop novel approaches that will effectively confront emerging diseases and biowarfare. Among the many topics discussed are smallpox, the Ebola virus, influenza, SARS, arenaviruses and flaviviruses. Each chapter discusses hypothetical strategies for the discovery of relevant antiviral agents, recent findings related to biochemistry or drug discovery, and advances in the further development of established leads in the area. Timely and informative, this book clearly delineates the efforts being made to develop new and effective broad-spectrum antiviral agents.